2009
DOI: 10.1099/mic.0.026641-0
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Las quorum sensing autoinducer suppresses growth and biofilm production in Legionella species

Abstract: Bacteria commonly communicate with each other by a cell-to-cell signalling mechanism known as quorum sensing (QS). Recent studies have shown that the Las QS autoinducer N-(3-oxododecanoyl)-L-homoserine lactone (3-oxo-C 12 -HSL) of Pseudomonas aeruginosa performs a variety of functions not only in intraspecies communication, but also in interspecies and interkingdom interactions. In this study, we report the effects of Pseudomonas 3-oxo-C 12 -HSL on the growth and suppression of virulence factors in other bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 35 publications
(35 reference statements)
0
37
0
Order By: Relevance
“…Interestingly, the Pseudomonas aeroginosa homoserine lactone autoinducer (3OC12-HSL) was recently shown to exert a bacteriostatic activity, and decrease biofilm formation of Lp1 . These effects are correlated to the transcriptional down-regulation of lqsR gene in Lp1 [29]. This finding suggests a connection between 3OC12-HSL and the uniquely identified QS system in Lp1 .…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Interestingly, the Pseudomonas aeroginosa homoserine lactone autoinducer (3OC12-HSL) was recently shown to exert a bacteriostatic activity, and decrease biofilm formation of Lp1 . These effects are correlated to the transcriptional down-regulation of lqsR gene in Lp1 [29]. This finding suggests a connection between 3OC12-HSL and the uniquely identified QS system in Lp1 .…”
Section: Introductionmentioning
confidence: 67%
“…The QS autoinducer 3OC12-HSL of P. aeruginosa which is involved in both intra and inter-species communication has recently been shown to suppress the biofilm production of Lp1 [29]. Thus, to test whether a QS system is involved in the transcriptional regulation of lpg2644 during biofilm formation, the Las QS 3OC12-HSL from P. aeruginosa was used as a model autoinducer.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Kimura et al (61) have reported that the 3-oxo-C12-HSL molecule itself also has competitive effects against other bacteria. 3-oxo-C12-HSL specifically suppresses growth and biofilm formation in Legionella pneumophila , although it does not show bacteriocidal or bacteriostatic actions against other Gram-negative bacteria that the authors tested.…”
Section: Interspecies Interaction Via N-acylhomoserine Lactonesmentioning
confidence: 99%
“…Our previous study demonstrated that 3-oxo-C12-AHL accelerated apoptosis in the neutrophil and monocytic cell lines U-937 and P388D1, but not in the epithelial cell lines CCL-185 and HEp-2 (35). On the other hand, 3-oxo-C12-AHL, but not any of its analogues, was found to suppress growth and biofilm formation in Legionella pneumophila, whereas no bactericidal or bacteriostatic action against other Gram-negative bacteria such as Serratia marcescens, Proteus mirabilis, Escherichia coli, Alcaligenes faecalis and Stenotrophomonas maltophilia was found (17). 3-oxo-C 12 -AHL may also possess some role in interspecies and inter-kingdom communication.…”
mentioning
confidence: 96%